2021
DOI: 10.1088/1361-665x/abe032
|View full text |Cite
|
Sign up to set email alerts
|

Heating and de-icing function in conductive concrete and cement paste with the hybrid addition of carbon nanotubes and graphite products

Abstract: This paper aims to study the viability of conductive cement paste and conductive concrete with the hybrid addition of carbon nanotubes (CNT) and graphite powder (GP) as a self-heating material for heating, ice formation prevention and de-icing in pavements. Different heating tests, ice-preventing tests and de-icing tests were performed with cement paste and concrete specimens. Results confirm that the conductive cement composites studied, with the addition of 1% CNT + 5% GP, exhibited heating, de-icing and ice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…Applying electrical potential to the conductive cement composites generates heating (Gomis et al, 2015). Previous studies used a various range of applied voltage to investigate generated heating, and these studies confirmed that increasing the applied voltage increased the heating performance of samples (Farcas et al, 2021;Galao et al, 2014;Gomis et al, 2015;Lee et al, 2017aLee et al, , 2020. Therefore, based on the findings of our previous study (Armoosh and Oltulu, 2019), the maximum available output voltage (60 V) in the DC power supply was used to investigate the heating performance of cement composites.…”
Section: Heating/cooling Testsmentioning
confidence: 55%
See 1 more Smart Citation
“…Applying electrical potential to the conductive cement composites generates heating (Gomis et al, 2015). Previous studies used a various range of applied voltage to investigate generated heating, and these studies confirmed that increasing the applied voltage increased the heating performance of samples (Farcas et al, 2021;Galao et al, 2014;Gomis et al, 2015;Lee et al, 2017aLee et al, , 2020. Therefore, based on the findings of our previous study (Armoosh and Oltulu, 2019), the maximum available output voltage (60 V) in the DC power supply was used to investigate the heating performance of cement composites.…”
Section: Heating/cooling Testsmentioning
confidence: 55%
“…For example, ice caused by the snow can damage the concrete structures; therefore, ice-melting technology should be developed to enhance their strength and durability. Recently, many researchers have focused on using self-heating techniques to melt the surface snow on concrete structures (Farcas et al, 2021; Mohammed et al, 2019; Rao et al, 2018; Sassani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies with a different matrix, a mathematical model which predicts that the degree of heating is adjustable with the applied voltage by means of classical physics equations (Fourier, Newton and Joule) was applied to simulate the heating behavior [ 48 , 49 ]. Using the equations of this model, all tests were simulated in order to verify that it could be used in different materials.…”
Section: Resultsmentioning
confidence: 99%
“…Materials with good conductivity, such as steel fiber [16,17], carbon fiber [18,19], erosion wire [20], steel shaving [16], graphite powder [13,21], carbon nanotube [22], carbon black [20] and graphene [23] can be used to increase the electrical conductivity of cementitious materials. Fig.…”
Section: Introductionmentioning
confidence: 99%